Ontology of Finance Redux - Dustin Breitling (&&& (Triple Ampersand Publishing), 2017)
“Ontology of Finance Redux” is an abridged version of Suhail Malik's long essay “The Ontology of Finance: Price, Power, and the Arkhéderivative” published in Collapse Volume VIII Edited by Robin Mackay. *** Interweaving the works of Jonathan Nitzan and Shimshon Bichler, Elena Esposito and Elie Ayache, Malik provides a tour de force critique of the critique of political economy to demand an engagement with the byzantine operation of finance. The essay is an examination of the array of derivative tools and their constitutive role in hedging and speculating futures. It explains how the organizing element of `Capitalization' via price renders all conceptions of temporality as a revisable, adaptable, and ultimately contingent operation. Malik's philosophical assertion is that the traditional notions of social order and norms have always been subject to perpetual restructuring. `Risk-Order'as the primary ingredient of `capital-power' poses a tremendous challenge not only for Marxist and neoclassic political economy but also for Left-Accelerationaism and its underlying neorational philosophies.
Keywords: P1; G12; 330; capital as power; differential accumulation; derivatives; finance; instability; power; price; risk; sabotage